Pengaruh Audit Fee , Audit Tenure, Reputasi Auditor Dan Komite Audit Terhadap Kualitas Audit Pada Perusahaan Saham Lq 45 Tahun 2020-2022 - Afiq Chamim Mubaroq; Lulu Syifa Fadhila; Inggrid Marisca Rubiyanty (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
This study aims to analyze the effect of audit fees, audit tenure, auditor reputation and audit committee on audit quality in LQ45 stock companies in 2020-2022. The population in this study were LQ45 stock companies, the sampling technique in this study used purposive sampling of 26 companies for three consecutive years 2020-2022. The data analysis method used in this research is logistic regression. The data used secondary data publishes information related to all research variables both in the form of annual reports and in other forms, the data is accessed through the Indonesia Stock Exchange (IDX) website collected by the documentation method and analyzed using SPSS version 25. The results showed that audit fee, audit tenure, auditor reputation and audit committee had no positive effect on audit quality in LQ45 stock companies in 2020-2022.